Development of three microbiologically safe, sensory acceptable food products as possible supplements to the diet of undernourished children (5 – 6 years) - Lombard, Matthys du Toit (Stellenbosch : Stellenbosch University, 2008)
Thesis (Msc Food Sc (Food Science))--Stellenbosch University, 2008.